Assessment of Occupational Safety and Health Practices among Workers in the Garment, Textile and Dyeing Industries in Abeokuta, Ogun State, Nigeria - Akintayo, W. L. (Africa Environmental Review Journal, 2020)
This study made a comparative analysis of the occupational safety and health practices among workers in the Garment, Textile and Dyeing industries in Abeokuta, Ogun State, Nigeria. Two research objectives guided the study. This study is a descriptive survey research designed conducted among all the 157 garment, textile and dyeing workers and the respondents from each of the three industries were selected using Stratified random sampling technique. Data was collected using an interviewer administered questionnaire. Data was processed using SPSS IBM version 20 and analyzed using descriptive and inferential statistics. Mean was used to answer the research objectives, while Analysis of Variance (ANOVA) was employed to see the effect of explanatory variables on dependent variable. Findings revealed that safety practices in an industry does not depend on the type of work it engaged in but was positively associated with being informed of safety precautions and being supplied with chemical information by supervisors. The study also apparently revealed that the prevalence of accident in industries is not as a result of safety equipment, but a combination of careless attitude of workers, and employer’s failure to enforce compliance to safety rules. Implications were drawn from the study and recommendations were made to workers and employers for benefiting the dividends of good safety practices.